Islamic Education and Family Mental Health: A Model of Development of Mental Disorders Patients through a Religious Approach in Paringan Ponorogo - Mahmudin, Afif Syaiful (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
In 2011, the people of Ponorogo were shocked by the news of the